Stem Cell Therapy in Patients with Chronic Nonischemic Heart Failure - Gregor Poglajen; Gregor Zemljič; Sabina Frljak; Andraž Cerar; Vesna Andročec; Matjaž Sever; Peter Černelč (Hindawi Limited, 2018)
Aim of the Review. The aim of this review is to discuss recent advances in clinical aspects of stem cell therapy in chronic nonischemic heart failure (DCMP) with emphasis on patient selection, stem cell types, and delivery methods. Recent Findings. Several stem cell types have been considered for the treatment of DCMP patients. Bone marrow-derived cells and CD34+ cells have been demonstrated to improve myocardial performance, functional capacity, and neurohumoral activation. Furthermore, allogeneic mesenchymal stem cells were also shown to be effective in improving heart function in this patient population; this may represent an important step towards the development of a standardized stem cell product for widespread clinical use in patients with DCMP. Summary. The trials of stem cell therapy in DCMP patients have shown some promising results, thus making DCMP apparently more inviting target for stem cell therapy than chronic ischemic heart failure, where studies to date failed to demonstrate a consistent effect of stem cells on myocardial performance. Future stem cell strategies should aim for more personalized therapeutic approach by establishing the optimal stem cell type or their combination, dose, and delivery method for an individual patient adjusted for patient's age and stage of the disease.